1995
DOI: 10.1083/jcb.128.6.1019
|View full text |Cite
|
Sign up to set email alerts
|

SNAP-25 is expressed in islets of Langerhans and is involved in insulin release.

Abstract: Abstract. SNAP-25 is known as a neuron specific molecule involved in the fusion of small synaptic vesicles with the presynaptic plasma membrane. By immunolocalization and Western blot analysis, it is now shown that SNAP-25 is also expressed in pancreatic endocrine cells. Botulinum neurotoxins (BoNT) A and E were used to study the role of SNAP-25 in insulin secretion. These neurotoxins inhibit transmitter release by cleaving SNAP-25 in neurons.Cells from a pancreatic B cell line (HIT) and primary rat islet cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
150
2
4

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(167 citation statements)
references
References 64 publications
11
150
2
4
Order By: Relevance
“…Although SNAP25 has not earlier been described in prostate, it has an established role in membrane trafficking and exocytosis for hormone secretion in other tissues, such as the pancreas (Sadoul et al, 1995). The basal cell profile was consistent with a proliferative phenotype, with expression of CXCL1, NBS1 and RPA, all of which encode proteins shown earlier to promote proliferation (Chiang et al, 2003;Li et al, 2004;Givalos et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Although SNAP25 has not earlier been described in prostate, it has an established role in membrane trafficking and exocytosis for hormone secretion in other tissues, such as the pancreas (Sadoul et al, 1995). The basal cell profile was consistent with a proliferative phenotype, with expression of CXCL1, NBS1 and RPA, all of which encode proteins shown earlier to promote proliferation (Chiang et al, 2003;Li et al, 2004;Givalos et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…These proteins are potential regulators of trafficking, docking, and fusion of secretory vesicles (50). Morphological and biochemical studies demonstrated the presence of VAMP-2 in insulin and in ␥-aminobutiric acid (GABA) secretory vesicles of ␤-cells (51), and cleavage of both VAMP-2 and SNAP-25 by tetanus or botulinum neurotoxins block insulin exocytosis in ␤-cells (52,53). The rab small G protein family consists of nearly 30 members implicated in intracellular vesicle trafficking (54).…”
Section: Resultsmentioning
confidence: 99%
“…The exocytosis of insulin-containing LDCV resembles that of neuronal synaptic vesicles [26] and employs a similar broad set of proteins, each of which plays a precise role. In particular, a direct implication in the control of insulin secretion has been established for several members of the exocytotic machinery, including SNAP25 [27], NSF [28], MUNC18-1 [29] and both SYT V and SYT IX [30]. However, the role of SYT IV and SYT VII in neurons and pancreatic beta cells is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%